Pharmacokinetics of Free Oxytetracycline and Oxytetracycline Loaded Cockle Shell Calcium Carbonate-Based Nanoparticle in BALB/c Mice - Idris, Sherifat Banke; Abdul Kadir, Arifah; Abdullah, Jesse F. F.; Ramanoon, Siti-Zubaidah; Basit, Muhammad Abdul; Abubakar, Md Zuki Z. A. (Frontiers in Veterinary Science, 2020)
The development and utilization of nano-antibiotics is currently gaining attention as a possible solution to antibiotic resistance. The aim of this study was therefore to determine the pharmacokinetics of free oxytetracycline (OTC) and oxytetracycline loaded cockle shell calcium carbonate-based nanoparticle (OTC-CNP) after a single dose of intraperitoneal (IP) administration in BALB/c mice. A total of 100 female BALB/c mice divided into two group of equal number (n = 50) were administered with 10 mg/kg OTC and OTC-CNP, respectively. Blood samples were collected before and post administration from both groups at time 0, 5, 10, 15, 30 minutes and 1, 2, 6, 24 and 48 hrs, and OTC plasma concentration was quantified using validated HPLC-UV method. The pharmacokinetic parameters were analysed using a non-compartment model. The Cmax values of OTC in OTC-CNP and free OTC treated group were 64.99 µg/ml and 23.53 µg/ml, respectively. OTC was detected up to 24 hr in OTC-CNP group as against 1hr in free OTC group following intraperitoneal administration. In OTC-CNP group, the plasma elimination rate of OTC was slower while half-life, area under the curve and volume of distribution were increased. In conclusion, the pharmacokinetic profile of OTC in OTC-CNP group differ significantly from free OTC. However, further studies are necessary to determine the antibacterial efficacy of OTC-CNP for treatment of bacterial diseases.